17β-Estradiol Attenuates Conduit Pulmonary Artery Mechanical Property Changes With Pulmonary Arterial Hypertension. Issue 5 (November 2015) - Liu, Aiping; Tian, Lian; Golob, Mark; Eickhoff, Jens C.; Boston, Madison; Chesler, Naomi C.
<x xml:space="preserve">Abstract</x> Pulmonary arterial hypertension (PAH), a rapidly fatal vascular disease, strikes women more often than men. Paradoxically, female PAH patients have better prognosis and survival rates than males. The female sex hormone 17β-estradiol has been linked to the better outcome of PAH in females; however, the mechanisms by which 17β-estradiol alters PAH progression and outcomes remain unclear. Because proximal pulmonary arterial (PA) stiffness, one hallmark of PAH, is a powerful predictor of mortality and morbidity, we hypothesized that 17β-estradiol attenuates PAH-induced changes in mechanical properties in conduit proximal PAs, which imparts hemodynamic and energetic benefits to right ventricular function. To test this hypothesis, female mice were ovariectomized and treated with 17β-estradiol or placebo. PAH was induced in mice using SU5416 and chronic hypoxia. Extra-lobar left PAs were isolated and mechanically tested ex vivo to study both static and frequency-dependent mechanical behaviors in the presence or absence of smooth muscle cell activation. Our static mechanical test showed significant stiffening of large PAs with PAH (P<0.05). 17β-Estradiol restored PA compliance to control levels. The dynamic mechanical test demonstrated that 17β-estradiol protected the arterial wall from the PAH-induced frequency-dependent decline in dynamic stiffness and loss of viscosity with PAH (P<0.05). As demonstrated by the in vivo measurement of PA hemodynamics via right ventricular catheterization, modulation by 17β-estradiol of mechanical proximal PAs reduced pulsatile loading, which contributed to improved ventricular–vascular coupling. This study provides a mechanical mechanism for delayed disease progression and better outcome in female PAH patients and underscores the therapeutic potential of 17β-estradiol in PAH.